2006
DOI: 10.1149/1.2138675
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Water Removal from a Polymer Electrolyte Fuel Cell

Abstract: Liquid water transport and removal from the gas diffusion layer ͑GDL͒ and gas channel of a polymer electrolyte fuel cell ͑PEFC͒ are studied experimentally and theoretically. In situ observations of the liquid water distribution on the GDL surface and inside the gas channel were made in an operating transparent PEFC. Liquid droplet formation and emergence from the GDL surface are characterized and two modes of liquid water removal from the GDL surface identified: one through droplet detachment by the shear forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
306
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(317 citation statements)
references
References 23 publications
8
306
1
2
Order By: Relevance
“…Visualization method is an effective way to observe the two-phase flow, which has been used for tube [15] or minichannel [16] recently. Researchers have studied the two-phase flow caused by liquid water inside PEMFCs by using the direct visualization method and transparent PEMFCs [17][18][19][20][21][22][23][24][25][26][27]. Yang et al [19] applied an optical PEMFC to study the mechanics of liquid water transport.…”
Section: Introductionmentioning
confidence: 99%
“…Visualization method is an effective way to observe the two-phase flow, which has been used for tube [15] or minichannel [16] recently. Researchers have studied the two-phase flow caused by liquid water inside PEMFCs by using the direct visualization method and transparent PEMFCs [17][18][19][20][21][22][23][24][25][26][27]. Yang et al [19] applied an optical PEMFC to study the mechanics of liquid water transport.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the conventional serpentine and straight channels [1], a conventional and interdigitated-switchable gas flow field was proposed to improve the cell performance under flooded conditions [2], and a self-draining stirred tank reactor cell was proposed for operations with low relative humidity gases [3]. To develop a detailed understanding of PEFC dynamics, a number of studies on the diagnostics of PEFC, such as on the measurement of the current density distribution and visualization of the water production behavior, have been conducted [3][4][5][6][7][8][9], and an overview was provided on the distributions of current density, high-frequency resistance, gas species and temperature, and including a two-phase visualization [1]. The effects of the distribution of the produced water and the gas composition on the cell performance were discussed using the measured results of the current density distribution [4,5], and the relationships between the local cell impedance and current density have also been investigated [3].…”
Section: Introductionmentioning
confidence: 99%
“…The water production behavior in the cathode gas flow channels has been investigated using a transparent fuel cell, and the relation between liquid water behavior and cell performance was demonstrated [6]. Liquid water removal from gas channels has also been characterized in detail [7]. The authors have observed phenomena related to water production behavior inside a cell, analyzed the effects on the current and temperature distributions across the reaction area [8], and reported the specific phenomena in the flow of condensed water and gas using cells with serpentine and straight channels [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, deficiency of water decreases the proton conductivity of the membrane and thus humidification of reactants is typically needed. Water management has a considerable effect on fuel cell performance and the process is highly sensitive to operational and material parameters [9][10][11][12][13]. Water transport inside the fuel cell has a close link to temperature distribution since water and oxygen diffusivity, saturation parameters, and reaction kinetics are all temperature dependent, see, e.g.…”
Section: Introductionmentioning
confidence: 99%